HYPNOBIRTHING PADA IBU HAMIL TRIMESTER KE III UNTUK MENGHADAPI PROSES PERSALINAN DI PUSKESMAS PUTRI AYU - Gustina Gustina (Jurnal Abdimas Kesehatan (JAK), 2019)
Backround: Childbirth is the process of expulsion from the conception of the uterus through the vagina to the outside world. In some cases, birth is a happy thing but in some cases it is a time of pain, fear, suffering and even death. Pain felt by the mother is an unpleasant sensory or emotional experience due to potential or actual tissue damage (Judha, 2012). One of the non-pharmacological techniques that can reduce pain by using hypnobirthing technique (Kozier, 2011). Target and uotcom: Trimester III Pregnant Women in antenatal care class, aims to improve the knowledge and skills of pregnant women about hypnobirthing techniques for readiness to face the labor process. Method implementation: Implementation: preparation of administration, socialization, implementation of hypnobirthing technique training and evaluation by interviewing the readiness of mothers before and after hypnobirthing technique training. Results : Before hypnobirthing training was performed in 10 third trimester pregnant women, 5 (50%) were ready, 4 (40%) were doubtful, and 1 (10%) was afraid of facing labor. After doing hypnobirthing training, the result is that 5 (50%) are more ready, 4 (40%) ready and 1 (10%) doubtful. Conclusion: Results before and after hypnobirthing technique training can be concluded that there is a change in maternal readiness in the face of labour. Suggestion : It is recommended that the Puskesmas conduct hypnobirthing technical training on regular and scheduled basis for pregnant women, especially in the third trimester of pregnancy.